Development of Pre-Clinical Assays Based on Tandem Mass Spectrometry to Investigate Gabaa Receptor Modulators - (:unkn) unknown (My University, 2017)
ABSTRACT DEVELOPMENT OF PRE-CLINICAL ASSAYS BASED ON TANDEM MASS SPECTROMETRY TO INVESTIGATE GABAA RECEPTOR MODULATORS by Margaret L. Guthrie The University of Wisconsin – Milwaukee, 2017 Under the Supervision of Professor Alexander (Leggy) Arnold Drugs are compounds that interact with a biological system to produce a specific biological response. The goal of drug discovery is to design and synthesize a pharmaceutical agent that will produce a desired biological effect. However, the in-vivo effects of a drug molecule cannot be predicted without a variety of test results prior to human clinical trials. In order to designate any drug compound as a leading candidate (or “lead” compound), it needs to show significant pharmacological activity, maintain a desirable metabolic half-life, and display minimal side effects and toxicity. Several in-vitro and in-vivo pre-clinical assays have been developed to measure metabolic parameters and aim to qualify, or rule out, compounds based on drug distribution within the body. The developments of these assays are presented herein. First, an assay was developed to estimate metabolic half-life of drug compounds in vitro using human and mouse liver microsomes by liquid chromatography-mass spectrometry (LC-MS). Secondly, a method for determination of pharmacokinetic (PK) parameters was developed and optimized using absolute quantitation by LC-MS/MS. Thirdly, metabolic stability was further estimated in cell suspensions and tissue homogenates, specifically using HepG2 cells as a model for hepatocytes, and rat brain as a model for illustrating stereochemical specificity within the brain enzymatic metabolism. Finally, to visualize the spatial distribution of small molecules in-vivo, matrix assisted laser desorption ionization tandem mass spectrometry (MALDI-MS/MS) was employed to image the distribution of drug compounds in whole tissue slices. By employing a variety of mass spectrometric techniques, we have been able to both assess the viability and follow the distribution of lead compounds from in-vitro sub-cellular fractions to whole cells through whole tissues and carry out in-vivo studies.
Keywords: HPLC; LC-MS/MS; Liquid Chromatography; MALDI; MALDI IMS; Mass Spectrometry